PENGEMBANGAN E-BOOK BERBANTUAN HEYZINE PADA MATERI INDONESIAKU KAYA ALAMNYA UNTUK MENINGKATKAN BERPIKIR KREATIF - Silma Hani; Didit Ardianto; Elly Sukmanasa (STKIP Subang, 2025)
The research employed the Research and Development (R&D) method using theADDIE model, which consists of the stages: Analysis, Design, Development,Implementation, and Evaluation. The validation results indicated that the feasibilityratings were 89.2% from the material expert, 91.6% from the media expert, and88.8% from the language expert, all classified as